KONDISI PENCEMARAN AIR SUNGAI CIPINANG JAKARTA - Yudo, Satmoko (Center for Environmental Technology, 2014)
Cipinang River is one of the thirteen (13) rivers flowing in Jakarta. In the area along the river, there are a variety of activities such as industrial activities, residential, shopping malls and hospitals. These activities each day issued wastewater into the river, so that the physical condition of the river is getting worse. To find out how much pollution in Cipinang river, we analyze the measurement data from Jakarta BPLHD, especially parameters such as BOD, COD, phosphates, detergents, organic matter and bacteria coli. The analysis showed that the pollution in the river downstream Cipinang looks very high, this indicator shows that the pollution comes from industrial waste and domestic waste from households, offices and shops. Some efforts to reduce pollution is to build domestic wastewater treatment both individual and communal. Supervision and decisive action must be taken by the government of Jakarta for industries which dispose of waste water without treatment as well as granting permission to discharge liquid waste (IPLC) for industrial tightened.Ã‚Â Keywords: Cipinang river, organic parameters, phosphat, detergent, coli bactery, industry pollution and domestic pollution